Investigating the Effectiveness of Serious Games in Educating Neonatal Resuscitation: A Systematic Review - Parisa Farshid; Kayvan Mirnia; Peyman Rezaei-Hachesu; Elham Maserat; Taha Samad-Soltani (Journal of Pediatrics Review)
Background: Neonatal resuscitation is a critical skill that requires regular training and practice; however, traditional training methods are often limited by accessibility, cost and engagement. Serious games (SGs) have emerged as a promising educational tool to address these challenges. This systematic review assesses the effectiveness of SGs in neonatal resuscitation education. Objectives: This systematic review assesses the effectiveness of SGs in neonatal resuscitation education. Methods: This systematic review followed the preferred reporting items for systematic reviews and meta-analysis guidelines and utilized a comprehensive search strategy across multiple databases (PubMed, Scopus, Web of Science, Embase, Cochrane and ProQuest) using keywords and MeSH terms related to neonatal resuscitation and SGs. Studies published in English up to July 25, 2024, focusing on SGs for neonatal resuscitation training were included. Two independent reviewers screened titles, abstracts, and full texts, resolving disagreements through discussion. Results: SGs were as effective as video lectures in improving neonatal resuscitation performance. Also, remote digital SGs provided interactive and enjoyable learning experiences for anesthesiologists and pediatric trainees. Paramedics and registered nurses significantly improved neonatal resuscitation performance and knowledge using SGs. Nursing students exhibited increased knowledge, problem-solving abilities and self-confidence with virtual reality-based SGs. Conclusions: SGs demonstrate promise as a complementary tool for neonatal resuscitation education. They can enhance knowledge acquisition, and skills development, and potentially improve motivation and engagement. However, further research is needed to optimize game design, investigate long-term learning outcomes, and assess skills transfer to clinical practice. Integrating SGs with traditional simulation-based training methods could offer a comprehensive and effective approach to training healthcare professionals in this critical skill set.